2015
DOI: 10.1177/2051013615595595
|View full text |Cite
|
Sign up to set email alerts
|

Safety, efficacy, and immunogenicity of Flublok in the prevention of seasonal influenza in adults

Abstract: Flublok is the first recombinant hemagglutinin (HA) vaccine licensed by the US Food and Drugs Administration for the prevention of influenza in adults aged 18 and older. The HA proteins produced in insect cell culture using the baculovirus expression system technology are exact analogues of wild type circulating influenza virus HAs. The universal HA manufacturing process that has been successfully scaled to the 21,000L contributes to rapid delivery of a substantial number of doses. This review discusses the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 39 publications
1
84
0
Order By: Relevance
“…Instead, it demands excellent viral clearance measures, such as those that have been developed by Protein Sciences Corporation to ensure the safety of their products (Post, 2010). Accordingly, Protein Sciences has administered Flublok® to nearly 2500 adults in five randomized, placebo- or active-controlled human clinical trials and successfully documented its safety (Cox et al, 2015). Like other experts in the field, we are well aware of this track record and, therefore, it should be obvious our analysis of the recent publication on Sf-rhabdovirus contamination of Sf9 L5814 cells is intended to provide a scientific assessment of the results and conclusions presented therein (Hashimoto et al, 2017), not, in any way, to criticize any product commercialized by Protein Sciences Corporation.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Instead, it demands excellent viral clearance measures, such as those that have been developed by Protein Sciences Corporation to ensure the safety of their products (Post, 2010). Accordingly, Protein Sciences has administered Flublok® to nearly 2500 adults in five randomized, placebo- or active-controlled human clinical trials and successfully documented its safety (Cox et al, 2015). Like other experts in the field, we are well aware of this track record and, therefore, it should be obvious our analysis of the recent publication on Sf-rhabdovirus contamination of Sf9 L5814 cells is intended to provide a scientific assessment of the results and conclusions presented therein (Hashimoto et al, 2017), not, in any way, to criticize any product commercialized by Protein Sciences Corporation.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…There are three types of seasonal influenza vaccines that are currently licensed for use in humans in the U.S.: 1) inactivated; 2) live attenuated; and 3) recombinant HA influenza vaccines[913]. Inactivated influenza vaccines and recombinant HA vaccines are administered intramuscularly (i.m.…”
Section: Current Influenza Vaccines and Their Limitationsmentioning
confidence: 99%
“…However, in recent years alternative vaccines have entered the US market, most notably a seasonal influenza vaccine made from recombinant hemagglutinin protein produced in insect cells (Flublok Ò , Protein Sciences Corporation). 84 Approved by the FDA for use in all adults, Flublok is classed as pregnancy category B, which means that studies in animals have shown no risk. While minimal data is currently available on Flublok use in pregnant women, such data should accrue with time now it is part of the seasonal vaccine market.…”
Section: Future Prospectsmentioning
confidence: 99%